2013
DOI: 10.1021/am401110n
|View full text |Cite
|
Sign up to set email alerts
|

Increasing Crystallinity for Improved Electrical Conductivity of TiO2 Blocking Layers

Abstract: In this Research Article, we present our results on the optimization of the TiO2 blocking layer to improve the efficiency of organic and hybrid solar cells and make them more competitive with standard silicon devices. The major aim of the present work is to increase the electrical conductivity within the TiO2 blocking layer to guarantee for efficient charge carrier transport and separation. This is realized by optimizing the calcination processes toward an increase in particle/domain size to increase the unper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 28 publications
1
16
0
Order By: Relevance
“…A record efficiency of 22.1% and excellent stability have been reported using mesoporous scaffolds deposited on charge extractors so that the perovskite would infiltrate the pores 21 . To enhance efficiency and improve device stability, materials such as TiO 2 , SnO 2 , phenyl-C61-butyric acid methyl ester (PCBM) as electron extractors and polymers 2,2′,7,7′-tetrakis ( N , N -di- p -methoxyphenyl-amine) 9,9′-spirobifluorene (Spiro-MeOTAD) poly(3,4-ethylenedioxythiophene)/poly(4-styrenesulfonate) (PEDOT:PSS) as hole extractors have been implemented using various deposition techniques 9 , 15 , 20 , 22 , 23 . The stability of PSCs exposed to 55–70% humidity range has been shown to improve by introducing chemical additives such as a thiocyanate (Pb(SCN) 2 ) 16 or phosphoric acid ω-ammonium chlorides 24 in the perovskite precursor solutions.…”
Section: Introductionmentioning
confidence: 99%
“…A record efficiency of 22.1% and excellent stability have been reported using mesoporous scaffolds deposited on charge extractors so that the perovskite would infiltrate the pores 21 . To enhance efficiency and improve device stability, materials such as TiO 2 , SnO 2 , phenyl-C61-butyric acid methyl ester (PCBM) as electron extractors and polymers 2,2′,7,7′-tetrakis ( N , N -di- p -methoxyphenyl-amine) 9,9′-spirobifluorene (Spiro-MeOTAD) poly(3,4-ethylenedioxythiophene)/poly(4-styrenesulfonate) (PEDOT:PSS) as hole extractors have been implemented using various deposition techniques 9 , 15 , 20 , 22 , 23 . The stability of PSCs exposed to 55–70% humidity range has been shown to improve by introducing chemical additives such as a thiocyanate (Pb(SCN) 2 ) 16 or phosphoric acid ω-ammonium chlorides 24 in the perovskite precursor solutions.…”
Section: Introductionmentioning
confidence: 99%
“…With a lower intensity and accordingly a lower crystallinity, a higher electrical resistance is observed as well. In References [44,45] it is also reported that a higher crystallinity leads to a higher electrical conductivity. It can be summarized that the electrical resistance of Ni thin films is lower when compared to Ni-20Cr thin films, independent from the substrate layer used.…”
Section: Resultsmentioning
confidence: 99%
“…The device with the SnS 2 CE annealed at 300 C (without phase transition) was also checked as a reference. The PCEs of the cells with these CEs was quite low (5.30% for SnS 2 /RGO and 5.01% for SnS 2 ), which might be due to their poor crystallinity impeding the charge transport process [26][27][28][29]. The DSSC with the SnS CE produced a PCE of 6.02% (V oc = 768 mV, J sc = 14.09 mA Á cm À2 , FF = 55.63%).…”
Section: Materials Characterizations With Xrd Sem and Temmentioning
confidence: 98%